Spatial statistical analysis of the distribution of komatiite-hosted nickel sulfide deposits in the kalgoorlie terrane, western Australia: clustered or not? - Mamuse, Antony; Porwal, Alok; Kreuzer, Oliver; Beresford, Steve (Society of Economic Geologists, 2016)
The spatial distribution of mineral deposits is a critical component of predictive estimation of undiscovered mineral resources. Nickel sulfide deposits in the Kalgoorlie terrane of Western Australia, the world’s premier province for komatiite-hosted nickel sulfide deposits, are generally perceived to be clustered. We apply distance-based spatial analysis methods (nearest neighbor and K function) to determine the spatial distribution pattern of nickel sulfide deposits in the Kalgoorlie terrane. Results of these spatial analyses indicate the komatiite bodies that contain the nickel sulfide deposits in the terrane are clustered. In contrast, nickel sulfide deposits within komatiite bodies are either randomly distributed or dispersed and not clustered. Therefore, the apparent clustering of nickel sulfide deposits within the Kalgoorlie terrane may be a mere expression of the underlying clustering of the host komatiite bodies. These findings have two main implications: (1) nickel exploration models implemented through area selection based on localization controls of favorable komatiite bodies, followed by direct detection of deposits within komatiite bodies have spatio-statistical validity, and (2) a Poisson distribution could be a plausible initial model for predicting the number of nickel sulfide deposits within a komatiite body.